Respostas
respondido por:
1
1° caso: Você irá substituir 100 no lugar de X e igualar a 100
f(x)=a.100+b=100
100a=100-b
a=-b
substituindo: f(x)= -b.100+b=100 => 100=100 certa.
2° caso: Você irá substituir -87,65 no lugar de X e igualar a -87,65
(x)=a.-87,65+b=-87,65
-87,65a=-87,65-b
a=-b
substituindo: f(x)= -b.-87,65+b=-87.65 => -87,65=-87,65 certa.
f(x)=a.100+b=100
100a=100-b
a=-b
substituindo: f(x)= -b.100+b=100 => 100=100 certa.
2° caso: Você irá substituir -87,65 no lugar de X e igualar a -87,65
(x)=a.-87,65+b=-87,65
-87,65a=-87,65-b
a=-b
substituindo: f(x)= -b.-87,65+b=-87.65 => -87,65=-87,65 certa.
ThiagoAguiar12:
Preparado para a ultima
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás